2017
DOI: 10.1089/vbz.2016.2078
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Toxoplasma gondii Infection in Common Quails (Coturnix coturnix) Intended for Human Consumption in Three Provinces of Northeastern China

Abstract: Common quails are nutritious food and are also used as medicine in some parts of the world. Until now, no information on Toxoplasma gondii infection in common quails intended for human consumption in China is available. Therefore, this study was carried out to determine the prevalence of T. gondii infection in common quails in six cities from Shandong, Liaoning, and Jilin provinces, China. Out of 620 common quails examined, 59 (9.52%) were seropositive for T. gondii by the modified agglutination test. T. gondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…In another survey from cold climate, only 3.9% of pigeons from Colorado, USA were seropositive (Dubey et al, 2010). Toxoplasma gondii antibodies were detected in 11.8% of 35 pigeons and 9.5% of 620 quails that were destined for human consumption in China (Cong et al, 2012(Cong et al, , 2017a. Finding of T. gondii DNA in the muscles of 6.4% of 390 quails indicates that the parasite was present in these birds destined for human consumption (Cong et al, 2017b).…”
Section: Herbivorous/insectivorous Birdsmentioning
confidence: 99%
“…In another survey from cold climate, only 3.9% of pigeons from Colorado, USA were seropositive (Dubey et al, 2010). Toxoplasma gondii antibodies were detected in 11.8% of 35 pigeons and 9.5% of 620 quails that were destined for human consumption in China (Cong et al, 2012(Cong et al, , 2017a. Finding of T. gondii DNA in the muscles of 6.4% of 390 quails indicates that the parasite was present in these birds destined for human consumption (Cong et al, 2017b).…”
Section: Herbivorous/insectivorous Birdsmentioning
confidence: 99%
“…Cong et al [6] reported a 6.4% infection rate in quails intended for human consumption in China. In another study from the same group, Cong et al [9] found a 9.52% infection rate in common quails from six cities in Shandong, Liaoning, and Jilin provinces in China. Alvarado-Esquivel et al [32] reported a 14.3% infection rate in quails from Mexico.…”
Section: Discussionmentioning
confidence: 92%
“…Among protozoan diseases, toxoplasmosis is particularly important as it is zoonotic and caused by the intra-cellular obligate apicomplexan parasite T. gondii [5]. Due to their ground feeding habits, birds, including those consumed by humans, can be infected with T. gondii and transmit the infection if their meat is not properly cooked [9,10]. Additionally, over 250 species of haemosporidians parasites, including Plasmodium, Haemoproteus, Leucocytozoon, and Fallisia, have been reported in birds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Toxo-DNA was detected by N-PCR in the tissues of quails, there were no significant differences recorded between the types of organs, the highest percentage was recorded in pectoral muscles 28% (7/25) and the lowest was in the heart 20% (5/25). These results were incompatible withCong et al, (2017) in China who recorded an infection rate of 6.41% (25/390) in common quails muscle tissues by N-PCR and with Al-khanak and Salman, (2021) who recorded the highest percentage in pectoral muscles 58.3% & the lowest percentage was recorded in the brain 62.5% while liver (70.8%) by N-PCR, and with Khan et al, (2020) in Pakistan was observed in chickens higher prevalence in liver 10.50% as compared to heart 9.5% and the lowest percentage was recorded in the muscles 7.11% by NPCR, and disagreed withMose et al, (2016) in Kenya who recorded 79.0% in the brain of chickens by N-PCR, and withHassan et al, (2020) in Egypt who revealed that the total infection rate was 7% in quail brain by histopathological examination. Finally disagreed with Al-Khalid, (2012) that recorded the prevalence rate in liver and heart was 57.14% and 25% respectively, while no amplification occurred in samples of brain by N-PCR that attributed to the capacity for tissue cyst formation varies among strains.…”
mentioning
confidence: 87%